Volumetric absorptive microsampling and conductive vial electromembrane extraction for the analysis of pharmaceuticals in whole blood - Reguli, Adam; Dowlatshah, Samira; Hansen, Frederik André; Štěrbová-Kovaříková, Petra; Pedersen-Bjergaard, Stig (Talanta, 2025)
Volumetric absorptive microsampling (VAMS) enables accurate collection of low blood volumes, independent of hematocrit. Electromembrane extraction (EME) is a sustainable sample clean-up technique; however, its wider applicability to extract analytes directly from VAMS tips remains unexplored. This study aimed to evaluate applicability of the first commercially available conductive vial EME device (with 2-nitrophenyl octyl ether as liquid membrane) for isolating 41 basic pharmaceuticals (log P 2-6) from 10 μL of blood on VAMS tips. The following extraction parameters were optimized: donor solution composition and volume, conductive vials size, applied voltage, extraction time and agitation speed. It was found that: 1/large conductive vials (600 μL) and 300 μL of donor solution provide higher process efficiency and reproducibility compared to smaller vials (200 μL) or larger donor solution volumes; 2/methanol in donor solution improve reproducibility and 3/sonication of VAMS tips in donor solution within a conductive vial prior to extraction enhances process efficiency. The EME protocol, followed by UHPLC-MS/MS analysis, was evaluated for process efficiency, linearity (1-1000 ng/mL), precision, and accuracy. Eleven analytes met most of the predefined acceptance criteria: process efficiencies 34.9-65.8 %, linearity (R2) 0.9933-0.9995, accuracy 85.9-111.1 % and precision 1.4-13.3 % RSD. The extraction was not impacted by hematocrit variation. EME demonstrated superior reproducibility and reduced matrix effects when compared to conventional VAMS tips treatment. This study confirms the reliability of a commercial conductive vial EME device for isolating basic pharmaceuticals from whole blood on VAMS tips, highlighting its potential for routine bioanalytical applications.
Keywords: Conductive vial electromembrane extraction; Sample preparation; Microextraction; Volumetric absorptive microsampling